Modeling and Stability Analysis of the Dynamics of Prey-Predator Population - Islam, Md Asraful; Ahmed, Tanvir (Jagannath University Journal of Science, 2024)
The aim of this work is to investigate the numerical study of prey-predator model and give a thorough overview of the existing research. Here we see instances that involve stability analysis, phase plane, and phase portrait, among others. Furthermore, a numerical simulation is shown to illustrate the results of the prey-predator model. This is to provide light on the procedures followed in order to arrive at the conclusions. The one-prey, one-predator principle is discussed in this article from multiple theoretical perspectives. Finally, for various parameter values and time intervals, we have demonstrated the phase portraits and the dynamic behavior of the pre-predator model. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 81−93